2019
DOI: 10.2196/12891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physician-Patient Communication in Online Health Communities on Patient Compliance: Cross-Sectional Questionnaire Study

Abstract: Background In China, the utilization of medical resources is tense, and most hospitals are highly congested because of the large population and uneven distribution of medical resources. Online health communities (OHCs) play an important role in alleviating hospital congestions, thereby improving the utilization of medical resources and relieving medical resource shortages. OHCs have positive effects on physician-patient relationships and health outcomes. Moreover, as one of the main ways for patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 93 publications
3
60
0
1
Order By: Relevance
“…To our knowledge, this is the first study to address the effects of patient empowerment gained through peer-to-peer OHCs on patient compliance with the proposed treatment. As such, this study extends prior research [14] showing that communication between physicians and patients in OHCs positively affects patient compliance. Lu and Zhang [14] found that when patients interact with physicians in OHCs, they have a better assessment of the quality of internet health information and they have better preferences during decision-making processes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, this is the first study to address the effects of patient empowerment gained through peer-to-peer OHCs on patient compliance with the proposed treatment. As such, this study extends prior research [14] showing that communication between physicians and patients in OHCs positively affects patient compliance. Lu and Zhang [14] found that when patients interact with physicians in OHCs, they have a better assessment of the quality of internet health information and they have better preferences during decision-making processes.…”
Section: Discussionsupporting
confidence: 87%
“…Although these communities can present disadvantages, such as the spread of misinformation and unreliable support or advice, OHCs play a role in heightening patients’ sense of empowerment as they feel better informed and guided by relevant others [13]. Prior research has shown that communication between the physicians and patients in these communities enhances patient compliance [14]. However, despite the considerable development of peer-to-peer OHCs, there is a lack of evidence regarding their effects on patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians view their role as responsible and trusted[ 96 ]. Lu et al[ 99 ] conducted a study about the use of online health communities (OHCs), which supports the previous information. They found that OHCs have a positive impact on patient compliance, which can be enforced even more by guiding physician-patient communication in the OHCs.…”
Section: Challengessupporting
confidence: 60%
“…The opportunity to share high-quality health information with patients and discuss the benefits, risks and costs of treatment options encourages the patients. Patients can participate in health-related decision-making, and the misunderstanding of information decreases[ 99 ]. eHealth applications not only change the way people inform themselves or track health information but also change communication.…”
Section: Challengesmentioning
confidence: 99%
“…Social media has become a key medium through which people communicate and share their health experiences. Although opportunities for users to provide health-related content on personal website home pages have been available for a while [26], the diffusion and increasingly broad application of social media since the mid-2000s have made these opportunities much easier [27][28][29]. The creation of content through social media applications, such as WeChat, QQ, Sina microblog, Baidu Post Bar, and Facebook has become especially popular [30,31].…”
Section: Discussionmentioning
confidence: 99%